Pengaruh Kompres Air Hangat Dengan Jahe (Zingiber Offcinale) Terhadap Penurunan Nyeri Osteoarthtritis Pada Lansia Di BPSTW Kecamatan Ciparay Kabupaten Bandung 2022 - Ida Widyanti; Deni Arisandi (Lembaga Pengembangan Kinerja Dosen, 2022)
: WHO estimates that 40% of the population over 70 years of age suffer from osteoarthritis and 80% had limitations. Figures Osteoarthtritis total reached 36.5 million people. In general pravelensi joint disease in Indonesia is very high at 30.3%. Traditional medicine to reduce pain osteoarthtritis lot of one with a ginger compress. The purpose of this study is to determine the effect Compress With Warm Water Ginger (Zingiber Offcinale) Decline Against Pain Osteoarthtritis On Elderly In 2016 Bandung Ciparay Bpstw type used in this research is the Pre- Experimental Design, with a research design using pretest and posttest one group design , Sample was 31 elderly people were selected by purposive sampling. Data collection was conducted test for normality using the Shapiro-Wilk test continued with univariate and bivariate analysis using mean using test T-test. The results showed no significant decrease in pain relief before being given a warm water compress of ginger with a value of 3:16 and after given a warm water compress ginger into 1.97 with a p-value of 0.000 or a≤0,05. Concluded that the provision of warm water compress with ginger for 4 days in Bandung Ciparay BPSTW shows the influence of the reduction in pain in the elderly who suffer osteoarthtritis. In the researchers suggested a non pharmacological therapy is expected to be applied by the elderly in addressing osteoarthtritis pain